Teaching Comparative Theology from an Institution's Mission - Bidlack, Bede (Teaching theology and religion, 2014)
Although comparative theology is a continuously growing method in the study of religion, it is still relatively new and not widely accepted in either confessional or secular institutions. Scholars may face difficulty when seeking their institutions' acceptance for a comparative theology course. One way of generating interest and approval for such a course is by designing it from the center of the institution's mission. Professors can look to the institution's mission as a resource for teaching comparatively. We offer four examples from Catholic institutions of how this might be done. Reid Locklin offers further insights in his response to our explorations.